2021
DOI: 10.1136/jnnp-2021-326072
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythm of ischaemic core progression in human stroke

Abstract: IntroductionExperimental stroke studies suggest an influence of the time of day of stroke onset on infarct progression. Whether this holds true after human stroke is unknown, but would have implications for the design of randomised controlled trials, especially those on neuroprotection.MethodsWe pooled data from 583 patients with anterior large-vessel occlusion stroke from three prospectively recruited cohorts. Ischaemic core and penumbra volumes were determined with CT perfusion using automated thresholds. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 12 publications
2
27
1
Order By: Relevance
“…This study proposed that the lower body temperature at night, among other factors, may have had a potential impact on their results [ 38 ]. Conversely, other studies have claimed that, although suffering a stroke at night is less frequent, they usually are more severe [ 26 , 39 ] and exhibit faster infarct progression [ 40 ], which supports the data observed in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…This study proposed that the lower body temperature at night, among other factors, may have had a potential impact on their results [ 38 ]. Conversely, other studies have claimed that, although suffering a stroke at night is less frequent, they usually are more severe [ 26 , 39 ] and exhibit faster infarct progression [ 40 ], which supports the data observed in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…The current large-scale study of ischemic stroke clinical presentation and course is consonant with recent smaller studies of ischemic stroke imaging. An analysis of CT perfusion imaging data in patients with anterior large vessel occlusion stroke found larger initial ischemic core volume with night-onset compared with day-onset strokes [29]. Core growth from onset to imaging proceeded was also faster in night-onset than day-onset strokes.…”
Section: Plos Medicinementioning
confidence: 98%
“…1,2 Epidemiological studies have found that the incidence of ischemic stroke is higher in the early hours of the morning, which has been reported to be up to 49% higher than in the other 18 hours of the day. 3 Furthermore, clinical outcomes of patients with acute ischemic stroke (AIS) also follow a circadian curve, with nighttime stroke resulting in faster infarct progression, 4 higher presenting neurologic severity, more frequent early neurological deterioration and worse 3-month functional outcome. 5 These findings motivated studies that investigate the temporal effects on the reperfusion therapy.…”
Section: Introductionmentioning
confidence: 99%